Boekpayoo Customary Ceremony of Ga-Dangme in Nungua: Culture Versus Law in Ghana’s Fight Against Child Marriages - Adom, Dickson (Udayana Journal of Law and Culture, 2024)
Child marriage has been an age-long problem in Ghana’s quest of protecting the rights and development of young girls. Though there are various international and domestic legal frameworks to assist the Ghana government in taking proactive steps in fighting against child marriages, there are some deep-rooted cultural practices commemorated in some Ghanaian traditional communities that seem to derail the government’s efforts. This paper aims to analyze the Boekpayoo customary ceremony organized by the Nungua Traditional Council in Ghana at the Gborbu temple on the 30 th of March 2024. It offers a deeper understanding of the appropriateness and legality of the Boekpayoo customary ceremony to show how Ghana struggles to end all forms of child or early marriage. This paper puts the customary ceremony under the lens of existing domestic and international legal frameworks and cultural anthropology perspectives. This paper has relied on and has been critically analyzed through secondary data from national and international legal instruments, cultural anthropology literature, and news reports. This study revealed that the procedure for the Boekpayoo ceremony, as well as the fitting appointment for occupying the position of Naa Yoomo Ayemuede, is legitimate, as it helps in the preservation and promotion of the place-identity history and culture of the Ga-Dangmes. However, the timing and selection of Naa Okromo need to be analyzed as they are not in accordance with the established national and international legal frameworks.